Physiological Biochemistry-Combined Transcriptomic Analysis Reveals Mechanism of Bacillus cereus G2 Improved Salt-Stress Tolerance of Glycyrrhiza uralensis Fisch. Seedlings by Balancing Carbohydrate Metabolism - Xiao, Xiang; Wang, Qiuli; Ma, Xin; Lang, Duoyong; Guo, Zhenggang; Zhang, Xinhui (Frontiers in Plant Science, 2022)
Salt stress severely threatens the growth and productivity of Glycyrrhiza uralensis. Previous results found that Bacillus cereus G2 enhanced several carbohydrate contents in G. uralensis under salt stress. Here we analyzed the changes in parameters related to growth, photosynthesis, carbohydrate transformation and the glycolysis (EMP) pathway-tricarboxylic acid (TCA) cycle by G2 in G. uralensis under salt stress. Results showed that G2 helped G. uralensis accumulating photosynthetic pigments during photosynthesis, which could further increase starch, sucrose and fructose contents during carbohydrate transformation. Specifically, increased soluble starch synthase (SSS) activity caused to higher starch content, which could induce α-amylase (AM) and β-amylase (BM) activities; increased sucrose content due to the increase of sucrose synthetase (SS) activity through up-regulating the gene encoding SS, which decreased cell osmotic potential, and consequently, induced invertase and gene encoding α-glucosidase that decomposed sucrose to fructose, ultimately avoided further water loss; increased fructose content required highly hexokinase (HK) activity to phosphorylate in G. uralensis, thereby providing sufficient substrate for EMP. However, G2 decreased phosphofructokinase (PFK) and pyruvate kinase (PK) activities during EMP. For inducing the TCA cycle to produce more energy, G2 increased PDH activity that enhanced CA content, which further increased ICDH activity and provided intermediate products for G. uralensis TCA cycle under salt stress. In sum, G2 could improve photosynthetic efficiency and carbohydrate transformation to enhance carbohydrate products, thereby releasing more chemical energy stored in carbohydrates through the EMP pathway-TCA cycle, finally maintain normal life activities and promote the growth of G. uralensis under salt stress.